Pursuing Information: A Conversation Analytic Perspective on Communication Strategies. Issue 3 (September 2014) - Burch, Alfred R.
<x xml:space="preserve">Abstract</x> Research on second language (L2) communication strategies over the past three decades has concerned itself broadly with defining their usage in terms of planning and compensation, as well as with the use of taxonomies for coding different types of strategies. Taking a Conversation Analytic (CA) perspective, this article examines the fine‐grained detail of a conversation between a first‐language speaker and an L2 speaker of Japanese and proposes a respecification of the notions of planning and compensation as socially viewable participant concerns, rather than as individualistic psychological constructs. Furthermore, the complex multifunctional and multimodal nature of interaction draws attention to the difficulty of categorizing usage of communication strategies into valid and generalizable taxonomical coding schemes. This article argues that CA can provide a useful methodological toolkit for exploring communication strategies from an interactional perspective, which focuses on L2 users' competence and communicative success rather than deficiency.